2021
DOI: 10.1111/jocs.15412
|View full text |Cite
|
Sign up to set email alerts
|

Mixed type total anomalous pulmonary venous connection: Early results and midterm outcomes of surgical correction

Abstract: Background and Aim of the Study The morphological heterogeneity of anomalous pulmonary venous drainage in mixed type total anomalous pulmonary venous connection (TAPVC) has important implications in preoperative diagnosis and surgical repair resulting in high mortality in these patients. Methods A retrospective review of 14 patients with mixed type TAPVC undergoing biventricular repair between January 2012 and December 2019 was conducted. A descriptive analysis was done, highlighting the anatomic variation, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The two examples in this article are the mixed TAPVC “3 + 1” type. It is simple to overlook one of them because of the varied position of pulmonary venous drainage ( 12 ). The main causes are the lack of a comprehensive and standard scan sequence, which ignores the scan of alternative ectopic drainage routes like the scan of the suprasternal fossa with or without vertical veins, and the content with detecting the common pulmonary venous cavity drainage channel.…”
Section: Discussionmentioning
confidence: 99%
“…The two examples in this article are the mixed TAPVC “3 + 1” type. It is simple to overlook one of them because of the varied position of pulmonary venous drainage ( 12 ). The main causes are the lack of a comprehensive and standard scan sequence, which ignores the scan of alternative ectopic drainage routes like the scan of the suprasternal fossa with or without vertical veins, and the content with detecting the common pulmonary venous cavity drainage channel.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed TAPVC: Mixed type TAPVC, which is complicated by more than 1 level of PV connection defect, is considered to be the most challenging type of TAPVC and sometimes requires combinations of surgical methods [ 28 ]. Few studies have reported clear conclusions as a result of the low morbidity (5–10% of patients with TAPVC); therefore, the reoperation rates of this type of TAPVC have not been clarified by large cohort studies [ 28 ]. It is difficult to pool surgical data from the published literature.…”
Section: Discussionmentioning
confidence: 99%